Methods for determining scattered solar radiation in order to increase the accuracy of forecasting hourly electricity generation by solar power plants - Sergey V. Mitrofanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Relevance. А simple and up-to-date methodology is needed to assess the potential of electricity that can be obtained from solar power plants installed in different regions. The difficulty in assessing the potential of solar energy lies in the presence of some factors that affect electricity generation and depend on random events. Such factors include, first of all, the sky clarity, the direction of photovoltaic panels strictly to the Sun, dustiness, and ambient temperature. The literature uses different approaches to assess the potential of solar energy. This paper presents a methodology for evaluating the generation of electricity by a solar panel having a continuous solar tracking system, taking into account the dustiness and temperature of photovoltaic panels. The technique has been tested on an existing physical model. Aim. To study the existing methods for assessing the potential of solar energy and to select the most suitable ones for the central part of Russia. Object. Solar power plants. Methods. Empirical and analytical methods. Using data obtained from an operating solar station, the adequacy of the proposed methodology was assessed. Results. The selected methods take into account the hourly sky clarity index, which made it possible, with sufficient accuracy for engineering techniques, to determine the daily power generation of a solar station with different angles of inclination of solar panels. This will improve the accuracy of estimating the potential of electricity generated by solar power plants, both with stationary photovoltaic panels and with solar tracking systems. Based on the conducted computational experiments and the analysis of data obtained from an operating solar station, the authors concluded that the technique presented in this paper allows us to determine with high enough accuracy the potential of electricity that can be produced in Russia by solar stations.